Impacts of temporary pedestrian streetscape improvements on pedestrian and vehicle activity and community perceptions. (December 2019) - Carlson, Jordan A.; Grimes, Amanda; Green, Maggie; Morefield, Thomas; Steel, Chelsea; Reddy, Ashleigh; Bejarano, Carolina; Shook, Robin P.; Moore, Tiffany; Steele, Laura; Campbell, Karen; Rogers, Eric
Abstract: Introduction: Micro-scale streetscape built environment attributes can support or inhibit physical activity over and above macro-scale community design factors. Quick build projects involve rapid and low-cost approaches for modifying streetscape design elements to improve pedestrian safety and support walking. This study evaluated quick build projects at two intersections in low-income neighborhoods. Methods: Two intersections were identified using a participatory process with community residents. The projects included painted crosswalks and temporary curb extensions to narrow the vehicle traffic lanes. Video and in-person direct observations were conducted before and during implementation to assess the number of pedestrians and vehicles using the intersection and vehicle/driver behaviors. Resident and stakeholder (e.g., public service workers) attitudes towards the projects were captured through surveys and interviews. Results: Pedestrian activity increased by 23% (p = 0.030) and vehicle activity did not change. The number of vehicles that failed to come to a complete stop at a stop sign decreased by 9% (p = 0.040) and the proportion of vehicles creating two lanes of traffic at the intersection of single-lane streets decreased from 70% to 0%. The mean rating regarding whether residents wanted the project to become permanent was 3.1 on a 1–4 scale, ranging from strongly disagree to strongly agree. The primary concerns noted related to burden to drivers. Stakeholders had positive attitudes towards the project but some noted concerns related to large vehicles' (e.g., fire engines) ability to make turns in the intersection. Conclusions: The findings suggest that inexpensive quick build streetscape improvements are promising for increasing pedestrian activity and walking. More research is needed to evaluate long-term outcomes of sustained quick build projects. Highlights: Streetscape interventions were conducted to improve pedestrian safety. The interventions resulted in an increase in the number of pedestrians (walkers). The interventions resulted in a decrease in unsafe driving behaviors. The interventions made residents feel safer, and overall attitudes were favorable.